Peroxygenase‐Catalyzed Oxyfunctionalization Reactions Promoted by the Complete Oxidation of Methanol. Issue 2 (26th November 2015) - Ni, Yan; Fernández‐Fueyo, Elena; Baraibar, Alvaro Gomez; Ullrich, René; Hofrichter, Martin; Yanase, Hideshi; Alcalde, Miguel; van Berkel, Willem J. H.; Hollmann, Frank
Abstract: Peroxygenases catalyze a broad range of (stereo)selective oxyfunctionalization reactions. However, to access their full catalytic potential, peroxygenases need a balanced provision of hydrogen peroxide to achieve high catalytic activity while minimizing oxidative inactivation. Herein, we report an enzymatic cascade process that employs methanol as a sacrificial electron donor for the reductive activation of molecular oxygen. Full oxidation of methanol is achieved, generating three equivalents of hydrogen peroxide that can be used completely for the stereoselective hydroxylation of ethylbenzene as a model reaction. Overall we propose and demonstrate an atom‐efficient and easily applicable alternative to established hydrogen peroxide generation methods, which enables the efficient use of peroxygenases for oxyfunctionalization reactions. Abstract : Fueled by methanol : Peroxygenases catalyze stereoselective oxyfunctionalizations by utilizing H2 O2 . To efficiently generate this oxidant in situ, a new enzymatic cascade process for the reductive activation of molecular oxygen with methanol as a stoichiometric reductant has been developed. This system was applied to the stereoselective hydroxylation of ethylbenzene to ( R )‐1‐phenylethanol.